UNDERSTANDING ALPHA GENERATION: EDUCATION AND CAREERS - Sihotang, Helena (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2025)
The purpose of this research is to analyse how the alpha generation including characteristics, education and career. The type of research used in this research is a literature study with the sources used include; textbooks, scientific journals, statistical references, research results published in national and international journals. The data analysis technique used is content analysis technique. The results of this study are that the alpha generation has characteristics such as: always connected to internet connections and social media, alpha generation has a specialisation in skills, likes things that are instant and practical, loves freedom, great desire for recognition, individualism, declining nationalism character. The vulnerabilities that the Alpha Generation will face are digital addiction, dependence on technology, mental health problems, dependence on parents, environmental issues and global uncertainty, education gap. Generation Alpha is predicted to be the generation with the highest level of education in history. However, they have a different learning style than previous generations. Social media platforms have a huge influence on their lives which also affects learning styles. Alphas expect visual, aural, and kinesthetic methods to be used in classroom management, and they are more prone to distraction, which is an important factor to consider in creating a teaching-learning environment, meaning that the learning process must coexist with technology. In 2031, the oldest Generation Alpha will begin to enter the workforce. Their jobs will be in the STEM (Science, Technology, Engineering and Maths) fields.